Preparation of hydrophobic carbon aerogel using cellulose extracted from luffa sponge for adsorption of diesel oil. Issue 23 (1st December 2021) - Yang, Hang; Sun, Jianfa; Zhang, Yi; Xue, Qiang; Xia, Shibin
Abstract: Carbon aerogel (CA) was prepared using the cellulose extracted from luffa sponge (LS). Trichlorosilane was employed to modify CA to enhance the adsorption capacity for diesel oil. The physical and chemical properties of aerogel, CA and modified CA were analyzed using XRD (X-ray diffraction), XPS (X-ray photoelectron spectroscopy), FTIR (Fourier Transform infrared spectroscopy), SEM (scanning electron microscope) and TGA/DTG (Thermogravimetric analysis/Derivative Thermogravimetry). Modified carbon aerogel (MCA) had better adsorption capacity for diesel oil (49.62 g/g) than aerogel (5.2 g/g) and CA (32.34 g/g). In addition, the adsorption capacity of MCA for other organics was also investigated, which indicated the abroad application scope for MCA. The reuse method (burning, suction filtration and pyrolysis) for diesel oil adsorption using MCA was investigated and pyrolysis shown the optimal effect for MCA regeneration. The cycle times of MCA for diesel oil adsorption was studied using pyrolysis to regenerate MCA and MCA still had good adsorption capacity for diesel oil (45.14 g/g) in the sixth use. This paper provides a novel strategy for resource utilization of LS and a fast and green method for diesel oil treatment.